Enterprise Credit Position and the Risk of Bankruptcy - Kowalik, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: This article discusses financial liquidity management in the context of enterprise bankruptcy. It looks at the basic causes leading to the bankruptcy of enterprises, including their credit position and how it changed in enterprises that have gone bankrupt. Research Design & Methods: The research methods were the study of the subject literature and the analysis of financial statements and reports of companies that had declared bankruptcy. The companies belonged to different sectors. Findings: Research findings confirmed the following hypothesis: in the time preceding the declaration of bankruptcy, the entity tends to be the recipient of trade credit. Implications / Recommendations: Drawn on the basis of evidence in the literature and empirical research, the conclusions for selected enterprises indicated that problems regarding the maintenance of financial liquidity, illustrated by the credit position, were an important reason bankruptcy was declared. Contribution: The research conducted in this article takes its spot among other analyses of the causes of corporate bankruptcy, which are common in the literature.